Alternative exercise methods for children with cerebral palsy: effects of virtual vs. traditional golf training - GERÇEK, NEJLA; UZUN, SELDA; TATAR, YAŞAR (TAYLOR & FRANCIS LTD, 2022)
Aim: Sport activities can increase the number of motor tasks performed by children with disabilities, helping to motivate these children to sustain life-long exercise. The aim of this study was to investigate the effects of virtual and traditional golf training on balance, muscle strength, lower extremity flexibility and aerobic endurance in children with cerebral palsy. Methods: 19 children with unilateral cerebral palsy were divided into two groups, each of them received either virtual (n = 9) or traditional (n = 10) golf training, for over 12 weeks with three days of a 60-minute session/day. The effect of golf training was assessed with the Gross Motor Function Measure-88, the Modified Ashworth Scale and Lateral Step Up, Curl Up, Six-Minute Walk, Sit and Reach, Modified Thomas, and balance tests. Results: Both training methods were associated with improved lower extremity flexibility and muscle strength, aerobic endurance and Gross Motor Function Measure-88 compared with the pre-training baseline values (p < 0.05). There was no difference found between virtual and traditional golf training groups except for balance and lateral step up tests (p > 0.05). Conclusions: Both virtual and traditional golf training applied for 12 weeks on children with unilateral cerebral palsy improved lower extremity functions and physical performance. The use of virtual and traditional training as a complementary application to reduce motor problems in children with cerebral palsy could enhance the sustainability of this type of training because of its edutainment features. Virtual golf has an important advantage over traditional golf in that (a) the latter can be expensive and inaccessible for people with disabilities, and (b) making virtual golf a safer activity.
Keywords: hemiplegia; golf; disabled children; adapted sports; virtual reality; 6-MINUTE WALK TEST; GROSS MOTOR FUNCTION; EXECUTIVE FUNCTION; REALITY; RELIABILITY; PROGRAM; BALANCE; PERFORMANCE; STRENGTH; THERAPY